2022
DOI: 10.1111/febs.16334
|View full text |Cite
|
Sign up to set email alerts
|

EHMT1/EHMT2 in EMT, cancer stemness and drug resistance: emerging evidence and mechanisms

Abstract: Metastasis, therapy failure and tumour recurrence are major clinical challenges in cancer. The interplay between tumour‐initiating cells (TICs) and epithelial–mesenchymal transition (EMT) drives tumour progression and spread. Recent advances have highlighted the involvement of epigenetic deregulation in these processes. The euchromatin histone lysine methyltransferase 1 (EHMT1) and euchromatin histone lysine methyltransferase 2 (EHMT2) that primarily mediate histone 3 lysine 9 di‐methylation (H3K9me2), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 121 publications
0
32
0
Order By: Relevance
“…Additionally, based on specific upregulation of EHMT1/2 expression in other cancer types 20 , this combinatory or even single EHMT therapy may be effective in treating those cancers as well. Lastly, our finding that EHMT therapy stimulates the activation of CD8 T cells has major implications for combining EHMT inhibitors with immunotherapy such as immune checkpoint blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, based on specific upregulation of EHMT1/2 expression in other cancer types 20 , this combinatory or even single EHMT therapy may be effective in treating those cancers as well. Lastly, our finding that EHMT therapy stimulates the activation of CD8 T cells has major implications for combining EHMT inhibitors with immunotherapy such as immune checkpoint blockade.…”
Section: Discussionmentioning
confidence: 99%
“…EHMT1 and EHMT2 are chromatin “readers” and “writers” that catalyze mono- and di- methylation of histone H3 lysine 9 (H3K9) residues 19 . Overexpression of EHMT1 and EHMT2 correlates with poorer survival outcomes, increased tumorigenesis, and therapy resistance in several cancer types 20 . In PARP inhibitor resistant ovarian cancer cells, both EHMT1/2 and H3K9me2 correlate with poorer survival outcomes and are causally linked to PARP inhibitor resistance 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycomponin 4 (Cbx4) is a ubiquitin-E3 ligase (Van Wijnen et al, 2021) that promotes the ubiquitin-like reaction at the lysine 917 (K917) site of PRDM16, inhibits ubiquitination degradation of PRDM16 and enhances adipose thermogenesis (Chen Q. et al, 2018a). Euchromatin histone methyltransferase 1 (EHMT1) is an essential brown adipose tissue (BAT)-enriched lysine methyltransferase (Nachiyappan et al, 2021;Gulyaeva et al, 2019). Chen Q. et al (2018a) found that Cbx4 promotes the ubiquitination of PRDM16, and the binding of EHMT1 to PRDM16 can further block the ubiquitination of other lysine residues and suppress the degradation of the PRDM16 protein (Chen Q. et al, 2018a;Ohno et al, 2013).…”
Section: Expression Regulationmentioning
confidence: 99%
“…Thus, both G9a and GLP are dysregulated in cancer and influence the expression of various downstream targets to promote proliferation, migration, and metastasis associated with poorer prognosis in patients [ 39 ]. Epigenome reprogramming occurs during the transition from normal to tumorigenic and metastatic states, resulting in altered methylation patterns.…”
Section: Ehmt1/glp and Ehmt2/g9a Dysregulation In Cancermentioning
confidence: 99%